Disrupting the characteristic twist motion; tailored in silico approach towards the design of plasmepsin inhibitors. (2022) - Kumi, Ransford Oduro; Yakubu, Elliasu Salifu; Agoni, Clement; Bidemi, Akawa Oluwole; Soliman, Mahmoud E.S.
Abstract: The effort to eradicate malaria has not yet been achieved, and the parasitic infection remains a global challenge. The burden stems from the worldwide dissemination of parasites resistant to commonly used chemotherapeutics and the scarcity of the malaria vaccine, Mosquirix. In the quest to augment malaria treatment, current focus has been geared towards plasmepsin (P). These classes of aspartic acid proteases are expressed at multiple stages of the parasite's life cycle and are implicated in host haemoglobin degradation and parasite dissemination in vivo ; elaborating their essentiality as therapeutic targets. Our earlier research examined the structural dynamics of WM382, a novel antimalarial compound, in relation to its enzyme inhibitory mechanism on plasmepsin IX (PMIX) and plasmepsin X (PMX). WM382 inflicts structural compactness on both proteases. The pharmacophoric moieties of WM382 were used in the present study to search the Zinc database for WM382 derivatives. The leads, ZINC06868602, ZINC09431717 and ZINC13367223 formed strong intermolecular bonds with the catalytic dyad Asp32 and Asp281. The flap regions generally move away from the binding pocket, divulging the active site to the inhibitor and keeping it near to the catalytic dyad. However, upon binding of the leads, the flap residues wrapped inward to surround the inhibitors, further restricting the characteristic twist motion of these proteases for enzyme activity. Likewise, for the experimental drug candidate WM382, the identified leads displayed high affinity for PMIX, with total binding free energies of leads estimated to be −33.45 kcal/mol, −30.33 kcal/mol and −29.67 kcal/mol, respectively. Evaluation of per residue energy composition indicated the catalytic dyad contributes immensely towards ligand binding. Results from our study suggest these compounds have better inhibitory prowess against PMIX. The potency of these chemicals should further be tested in the experimental laboratory to evaluate their usefulness. Graphical abstract: Image 1